Analisis Kesulitan Siswa dalam Menceritakan Kembali Isi Cerita Kelas IV SD Negeri Tempaling Rembang - Puryati, Anggita Yuli; Budiman, Muhammad Arief; Listyarini, Ikha (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to analyze students' learning difficulties in retelling stories and find out the factors that influence students' difficulties in retelling stories. This study uses a qualitative research method with a descriptive approach. In this study, researchers used several methods to collect data, including: observation, interviews, questionnaires (questionnaires), and documentation. The results of this study indicate that the highest student error is found in retelling the contents of the story that has been read, while the lowest student error is in student understanding. From the percentage of student errors, it shows that most students still have difficulty in retelling the content of the story, do not know the intrinsic and extrinsic elements of the story, the applied teacher learning style, lack of student response, and lack of student focus in learning. In addition, student difficulties can be influenced by internal factors and external factors.